EFEKTIVITAS PENGELOLAAN KEUANGAN DESA MULIA SUBUR KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN TAHUN 2023 - Dela Helmalia; Khotami Khotami (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2024)
This research aims to determine the financial management process of Village Funds in Mulia Subur Village, Pangkalan Kuras District, Pelalawan Regency. The principle of effectiveness is needed in managing village finances, which is one of the basics of how the implementation and distribution of village finances can be allocated well or not. Then information related to Village financial management should be known by various parties because it must be open. This research was carried out with the aim of determining the level of effectiveness in the use of Village finances, especially Village Funds in Mulia Subur Village, based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014 which includes planning, implementation, administration, reporting and accountability and supervision. This research uses a descriptive survey type and qualitative methods. To achieve the research objectives, researchers used data collection techniques, namely observation, interviews and documentation. This research uses the Prosperity theory which contains several assessment indicators (a) Accuracy of use of natural resources (b) Accuracy of use of available time (c) Accuracy of equipment or equipment (d) Accuracy of use of human resources (e) Accuracy of use Budget. The results of this research show that in financial management, especially Village funds, it is good enough but not effective enough so that the use of the budget is still not on target.